PENGARUH PERUBAHAN TUTUPAN LAHAN TERHADAP ALIRAN PERMUKAAN PADA SUB DAS KAMPAR KANAN - jefrizon jefrizon (Racic : Rab Construction Research, 2021)
Kampar watershed has a length of 580 km, with a catchment area of 21,086 km2, a maximum discharge of 2,200 m3 / s, a minimum discharge of 49 m3 / s. The largest level of damage in 4 major watersheds in Riau Province is located in the Kampar watershed, reaching 5,986 hectares. This study aims to analyze the effect of changes in land cover on surface runoff in the right sub-watershed using SWAT (hydrological model (soil water assessment tool). From the research results, changes in land use from 2009 to 2018 tend to increase precipitation from 3866.33 mm to 4687.94. Significant changes occurred in the water yield or the total amount of water entering the main river during the simulation period from 1722.65 mm to 3633.75 mm. The results of the calibration using the monthly discharge data from 2010 - 2011, the results of observations and predictions on the Lake Bingkuang SPAS were 276.70 m3 / s and 354.98 m3 / s. The results of the validation using the monthly discharge data for 2018 are 115.63 m3 / s and 93.03 m3 / s. The weight value and score of each performance of the right Kampar Sub-watershed in 2009 - 2018 shows that the percentage of vegetation cover (PPV) with a weight of 20%, a score of 0.5. Flow Regim Coefficient with a weight of 5%, a score of 0.75, while the annual flow coefficient with a weight of 5%, score, 0.5. The total number of watershed performance assessments with a weight of 30%, a score of 1.75, and the results of the assessment is 16.25 so that the performance results of the right Kampar Sub-watershed is 0.54.